Surface engineered CoP/Co3O4 heterojunction for high-performance bi-functional water splitting electro-catalysis. Issue 47 (24th November 2021) - Li, Xintong; Liu, Yizhe; Sun, Qidi; Huang, Wei-Hsiang; Wang, Zilong; Chueh, Chu-Chen; Chen, Chi-Liang; Zhu, Zonglong
Abstract : The s-CoP/Co3 O4 is employed as bi-functional catalysts towards HER and OER. A current density of 10 mA cm −2 can be achieved at an overpotential of 211 mV vs. RHE in OER and the overpotential is only 106 mV vs. RHE at a current density of −10 mA cm −2 in HER. Abstract : In the electrochemical water splitting process, integrating hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in the same electrolyte with the same catalyst is highly beneficial for increasing the energy efficiency and reducing the fabrication cost. However, most OER catalysts are unstable in the acidic solution, while HER shows poor kinetics in the alkaline solution, which hinders the scale-up application of electro-catalytic water splitting. In this work, a CoP/Co3 O4 heterostructure is firstly fabricated and then O and P defects are introduced via surface engineering (s-CoP/Co3 O4 ). The as-prepared material was employed as the catalyst towards electrochemical water splitting in an alkaline environment. In alkaline HER, a current density of −10 mA cm −2 can be achieved at an overpotential of 106 mV vs. RHE. In the OER process, the overpotential of s-CoP/Co3 O4 electrode is only 211 mV vs. RHE at 10 mA cm −2 in 1 M KOH, and the corresponding Tafel slope is only 58.4 mV dec −1 so that the s-CoP/Co3 O4 electrode could be used as the bifunctional catalyst for alkaline water splitting. This work provides a simple and low-cost approach to fabricate a Co-based heterojunction electrode with unsaturated metal sites to improve the electro-catalytic activities towards water splitting.